Police Taser Utilization : the Effect of Policy Change. - Miller, Michael E. (Criminal justice (LFB Scholarly Publishing LLC), 2010)
This work examines the effect of policy changes within the Use-of-Force Continuum on taser usage and officer's perceptions of taser effectiveness. Data from 890 encounters during two years were analyzed to examine how changes in policy have effected taser use. Findings support that after the change, the frequency of taser use decreased, while the levels of suspect resistance increased. The frequency and severity of suspect injuries did not change and the number of officers injured was unchanged. Officers perceived an increased risk of harm to themselves as a result of the change, but this was.